Hubungan Status Gizi dan Kualitas Hidup Lanjut Usia - Mega Nurul Anwar; Faishol Roni; Arif Wijaya (Jurnal Insan Cendekia, 2022)
Quality of life is a very important outcome measure for health. Health itself is the life expectancy of every human being, but as a way to improve the quality of life, it is necessary to have sufficient status. Nutritional status that is reduced or excessive can have an impact on the quality of life of the elderly. The purpose of this study was to determine the relationship between nutritional status and quality of life of the elderly. This study uses the Literature Review method with two databases, namely Google Scholar and Crossref. The results showed that there were 10 journals that had been reviewed with the conclusion that 9 journals had a significant relationship between nutritional status and quality of life of the elderly, and 1 journal had no relationship between nutritional status and quality of life of the elderly. The conclusion is that there is a relationship between nutritional status and quality of life in the elderly.